2020
DOI: 10.1002/anie.202007595
|View full text |Cite
|
Sign up to set email alerts
|

Atropisomerism in Diarylamines: Structural Requirements and Mechanisms of Conformational Interconversion

Abstract: In common with other hindered structures containing two aromatic rings linked by as hort tether,d iarylamines may exhibit atropisomerism (chiralityd ue to restricted rotation). Previous examples have principally been tertiary amines, especially those with cyclic scaffolds.L ittle is knowno ft he structural requirement for atropisomerism in structurally simpler secondary and acyclic diarylamines.I nt his paper we describe as ystematic study of as eries of acyclic secondary diarylamines,and we quantify the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…Upon protonation of the nitrogen center with an acid, the barrier of the rotation around the C−N single bond is dramatically lowered to Δ G ≠ =16.3 kcal mol −1 and racemization is complete in 10 min. A similar behavior was observed in acyclic diarylamines by the Clayden group [78] . This dynamic behavior is attributed to the pyramidalization of the nitrogen center involved in the restricted bond rotation.…”
Section: Controlling the Speed Of Molecular Rotorssupporting
confidence: 72%
“…Upon protonation of the nitrogen center with an acid, the barrier of the rotation around the C−N single bond is dramatically lowered to Δ G ≠ =16.3 kcal mol −1 and racemization is complete in 10 min. A similar behavior was observed in acyclic diarylamines by the Clayden group [78] . This dynamic behavior is attributed to the pyramidalization of the nitrogen center involved in the restricted bond rotation.…”
Section: Controlling the Speed Of Molecular Rotorssupporting
confidence: 72%
“…Two sets of peaks are observed by 1 H NMR spectroscopy, with the ratio of two apparent diastereomers, (S, S)-4a and (S, R)-4a, varying as a function of different NMR solvents (see SI section 14.3). While various phenomena might account for this observation (atropisomerism and conformational isomerism), 14,18,19,20 we speculated instead that this phenomena is due to slow epimerization of the malonate stereocenter via ketoenol tautomerization. To confirm the nature of the observed isomers, we performed a variabletemperature (VT) 1 H NMR and deuterium exchange experiments.…”
Section: Product Distribution Hmentioning
confidence: 88%
“…89 Clayden has recently reported a detailed study on the conformational stability of 2,2'-di-ortho-substituted diarylamines, wherein they observed that the size of ortho substituents on the different aryl rings can have a marked effect on the conformational profile, with larger substituents leading to a more perpendicular preferred conformation, and the possibility for stereochemical stability as demonstrated with compound 65 and 66 (Scheme 12a). 90 Work by Kawabata has demonstrated that the stereochemical stability of diaryl amines could be increased by an intramolecular N-H-N hydrogen bond (Scheme 12b). 91 Essentially, the hydrogen bond locked one of the atropisomeric axes into a planar conformation, preventing "gearing" mechanism of racemization.…”
Section: Atroposelective Lewis Acid Catalyzed Halogenation Towards Atropisomeric N-aryl Quinoidsmentioning
confidence: 99%